Smart Healthcare Monitoring System - Sowmya, V.; Dharani, K.; Vishalini, A.J.; Dharshini, C. Priya; Sujitha, R. (Journal of ISMAC, 2023)
Nowadays, extreme priority is focused on health, due to the out- break of Corona virus, to ensure precautions before any illness. In many circumstances, people tend to forget the importance of health and fail to monitor the health parameters, such as temperature, heart rate, and so on, due to work and busy schedules. Therefore, a smart healthcare system has been proposed in this research, wherein five sensors such as MAX30100 sensor, DS18B20 sensor, DHT11 sensor, MQ9, and MQ135 sensor which sense the patient and patient’s room conditions, are used. The obtained values are displayed in the web server, through which the patient’s condition is communicated to the hospital staff, where they can detect and evaluate the current health status of the patient. This approach will enhance the current healthcare system, by potentially saving many lives. Furthermore, medication should also be taken at the right time to improve the state of health which is too difficult for old patients and those who give less preference to health than work. Hence, a pill reminder system which uses IR sensor and a buzzer to remind the patients regarding the proper intake of medication is also designed.